Pengaruh Kekuatan Otot Terhadap Kecepatan Renang Gaya Bebas Club Renang Bintang Khatulistiwa Pontianak - Rio Wardhani (Sport Pedagogy Journal, 2022)
The  purpose  of  the study. (1) to determine the effect of arm muscle strength on the speed of freestyle swimming in the athletes of the Bintang Khatulistiwa Club, Pontianak; (2) to determine the effect of leg muscle strength on the speed of freestyle swimming in the athletes of the Bintang Khatulistiwa Club, Pontianak; (3) to determine the effect of arm and leg muscle strength on the speed of freestyle swimming in Bintang Equator Club athletes.Materials and methods. This type of research was conducted by observational by measuring arm muscle strength with a push up test and a leg muscle strength test using a half squad, with a population of 20 male swimmers at the Bintang Khatulistiwa Pontianak swimming club with a total sampling technique. The data collection technique was in the form of measurement and using a tool in the form of a freestyle swimming speed test. This research was conducted for two months.Results. The results based on the hypothesis of the effect of arm muscles and leg muscles on swimming 50 meters freestyle obtained Fcount of 0.719 with a significance value of 0.402 is 0.05 then Ho is accepted.Conclusions. The results of the freestyle swimming speed test for the Bintang Equator Club swimming athletes, (1) there is an effect of arm muscle strength through pull ups for each athlete on the 50 meter freestyle swimming speed. (2) there is an effect of leg muscle strength through half squats on each athlete on the speed of 50 meters freestyle swimming. (3) there is an effect of arm muscle strength through pull ups and leg muscle strength with half squad on each athlete on the 50 meter freestyle swimming speed. Keywords: Hands, Legs, Freestyle swimming